MicroRNA-Based Separation of Cortico-Fugal Projection Neuron-Like Cells Derived From Embryonic Stem Cells - Sunohara, Tadashi; Morizane, Asuka; Matsuura, Satoshi; Miyamoto, Susumu; Saito, Hirohide; Takahashi, Jun (Frontiers in Neuroscience, 2019)
The purification of pluripotent stem cell-derived cortico-fugal projection neurons (PSC-CFuPNs) is useful for disease modeling and cell therapies related to the dysfunction of cortical motor neurons, such as amyotrophic lateral sclerosis or stroke. However, no CFuPN-specific surface markers for the purification are known. Recently, microRNAs (miRNAs) have been reported as alternatives to surface markers. Here we investigated this possibility by applying the miRNA switch, an mRNA technology, to enrich PSC-CFuPNs. An array study of miRNAs in mouse fetal brain tissue revealed that CFuPNs highly express miRNA-124-3p at E14.5 and E16.5. In response, we designed a miRNA switched that responds to miRNA-124-3p and applied it to mouse embryonic stem cell (ESC)-derived cortical neurons. Flow cytometry and qPCR analyses showed the miRNA-124-3p switch enriched CFuPN-like cells from this population. Immunocytechemical analysis confirmed vGlut1/Emx1/Bcl11b triple positive CFuPN-like cells were increased from 6.5% to 42%. Thus, our miRNA-124-3p switch can uniquely enrich live CFuPN-like cells from mouse ESC-derived cortical neurons.